Objectivity of the Liaison in the Iraqi Media Institutions (Al Mada, Azzaman, Al-Sumaria, Aletejah Instituations & Satalite Channels as a Model) - Feidhi, Anmar Waheed (ALBAHITH ALALAMI, 2013)
Objectivity is the common denominator between the qualities and elements of a news story that is described as the mother of journalistic arts. When there is doubt about the authenticity of the information contained in the press, whether readable, audible or visual, it means that there is an imbalance in objectivity. When, furthermore, there is an incorrect and intentional use of words in order to influence readers, it means to move away from objectivity as a necessary element in the success of the media institution; and the success of its editorial material.But the objective interpretation may take several dimensions to the liaison. For the purpose of grasping the interpretation of objectivity among those liaisons working in the Iraqi media institutions, this research came up to the surface to highlight a subject that everybody circulates. Yet, the precise definition of the interpretation that agreed upon was not clear. Therefore, the problem of the research is limited to identify objectivity most agreed with the liaison in the Iraqi media institutions.The aim of the research is limited to identifying and diagnosing the most agreed interpretation among the respondents of the liaisons in the Iraqi media institutions, and diagnosing the vision of the liaisons of the objectivity, and how far can get to be available in the Iraqi media institutions through the press material provided.The research was limited to the staff of the editorial staff, because they are the liaisons, as the establishment of the press message lies on them. The researcher adopted the survey method in surveying the views of the respondents and their views and interpretations of objectivity in four Iraqi media institutions: Al Mada, Azzaman, Al-Sumaria, Aletejah.Where the first and second ones represent press institutions, while the third and fourth ones represent satellite channels.This research gave us that the interpretation of objectivity of the liaison in the Iraqi media institutions varies from one to another according to his view of a subject.